Lycée Essay (3): When a Truth is that Old, It is on its Way to Becoming a Lie - Gramsci, Antonio (International Gramsci Journal, 2024)
The subject of Gramsci’s essay, here in its English version, is taken from a paraphrase of words in Henrik Ibsen’s 1882 play An Enemy of the People: “Truths, in getting old, become errors”. Each generation has had its syntheses, truths following one another, each believed by its supporters but excluding the others. Intellectual ruins and contradictory substrata of human consciousness are the outome, and even science has not escaped this débacle. Contradictory truths have led even to massacres and reprisals, with the destruction of society’s dynamic and progressive aspects. Some truths are long-lasting, such as the Ptolemaic universe or the existence of God, whose mummi-fied corpse can still however make its presence felt. Many contemporary problems can be traced back to old truths which – through official compromise and hypocrisy – still have to be respected. Humanity will construct other, more rational truths, in order to reach some destiny, but we cannot know if this will consist of annulment or deification.